2020
DOI: 10.2519/jospt.2020.9071
|View full text |Cite|
|
Sign up to set email alerts
|

Young Athletes Who Return to Sport Before 9 Months After Anterior Cruciate Ligament Reconstruction Have a Rate of New Injury 7 Times That of Those Who Delay Return

Abstract: Objective To investigate the association between sustaining a second anterior cruciate ligament (ACL) injury and (1) time to return to sport, (2) symmetrical muscle function, and (3) symmetrical quadriceps strength at the time of return to sport in young athletes after primary ACL reconstruction. Design Prospective cohort study. Methods Patient demographics and results from 5 tests of muscle function (2 strength tests and 3 hop tests) were extracted from a rehabilitation registry. A questionnaire was sent to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
110
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 27 publications
4
110
0
3
Order By: Relevance
“…This is positive given that previous studies have shown a marked increase in risk for further injury in athletes who return to sport before 9 months. 1,5 The delay in return to competitive sport did not reduce overall graft rupture or contralateral ACL injury rates at between 3 and 5 years postoperatively, and 33% of patients sustained at least 1 further ACL injury (graft rupture or contralateral ACL injury). Even when patients were categorized according to the actual time taken to return to competitive sport (before versus after 12 months), 32% who returned after 12 months sustained a subsequent ACL injury.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is positive given that previous studies have shown a marked increase in risk for further injury in athletes who return to sport before 9 months. 1,5 The delay in return to competitive sport did not reduce overall graft rupture or contralateral ACL injury rates at between 3 and 5 years postoperatively, and 33% of patients sustained at least 1 further ACL injury (graft rupture or contralateral ACL injury). Even when patients were categorized according to the actual time taken to return to competitive sport (before versus after 12 months), 32% who returned after 12 months sustained a subsequent ACL injury.…”
Section: Discussionmentioning
confidence: 94%
“…However, a recent study, which followed 159 patients aged 15 to 30 years who had mostly hamstring tendon grafts, found that returning to strenuous sports before 9 months after ACLR surgery was associated with a 7-fold increased rate for a second ACL injury compared with returning after 9 months. 1 While these studies show contradictory findings related to the timing of return to sport and subsequent ACL injury, the age range of patients varied, and as such, there may be merit in delaying a return to sport for younger patients. However, there is a paucity of data from which to draw robust conclusions.…”
mentioning
confidence: 99%
“…Taken together, patients with ACL injuries may experience a loss of neural efficiency to engage in motor control, thereby contributing to both 1) impaired motor performance during dual-tasking or unanticipated movements and 2) an increased risk of secondary injury when attempting to rapidly increase motor complexity and environmental stimuli during early return to sport. 23,[63][64][65][66][80][81][82]…”
Section: Acl Injury Associated Neurocognitive Motor Planning Brain Activationmentioning
confidence: 99%
“…These results are in line with most of the previous studies evaluating different test batteries, mainly including strength and hop performance tests. 5,27,44,45 However, 2 previous studies found an association between results in test batteries and sustaining a second ACL injury, but each test alone in the test batteries did not predict a second ACL injury. 25,43 Although there are no objective criteria 17 or test after an ACLR that can predict who will sustain a new injury, 18 it is considered the best approach to evaluate different components and use a battery of tests to inform the return to sport decision.…”
Section: Discussionmentioning
confidence: 91%